"The Role of Artificial Intelligence in Enhancing the Efficiency of Administrative Contracts: Towards More Effective and Transparent Governance" - Sounds Alb ashier Ali MOs bah (Journal of Scientific and Human Dimensions, 2026)
It is well acknowledged that there are challenges facing the efficiency of administrative contracts, and perhaps technological advancements may contribute to addressing these issues, especially since artificial intelligence has been relied upon in many legal fields, with administrative contracts being among the most significant. To what extent can the implementation of these contracts be absorbed by the specialized administrative bodies responsible for concluding administrative contracts and their ability to execute them? Furthermore, how can artificial intelligence be utilized in drafting these contracts, determining the relevant laws and regulations, reviewing and analyzing them, and identifying any ambiguous clauses within them? Additionally, it can provide opinions that assist in decision-making regarding the improvement of the quality of new contracts, analyze potential risks, and offer recommendations on necessary measures and managing the relationship between contracting parties to enhance efficiency and improve the contracts concluded by the administration, as well as the ability to monitor their execution according to the agreed-upon terms. Moreover, it is crucial to avoid the flaws associated with the applications of artificial intelligence, such as algorithmic bias towards parties in administrative contracts, privacy breaches, data leaks and manipulation, and the high costs of these applications, all while there is a complete- absence of legislation establishing strict laws against their misuse